Compression of a mixed antiproton and electron non-neutral plasma to high densities - Aghion, Stefano; Demetrio, Andrea; Müller, Simon R.; Oberthaler, Markus K.; Zimmer, Christian (The European physical journal. D, Atomic, molecular, optical and plasma physics, 2018)
We describe a multi-step “rotating wall” compression of a mixed cold antiproton-electron non-neutral plasma in a 4.46 T Penning-Malmberg trap developed in the context of the AEḡIS experiment at CERN. Such traps are routinely used for the preparation of cold antiprotons suitable for antihydrogen production. A tenfold antiproton radius compression has been achieved, with a minimum antiproton radius of only 0.17 mm. We describe the experimental conditions necessary to perform such a compression: minimizing the tails of the electron density distribution is paramount to ensure that the antiproton density distribution follows that of the electrons. Such electron density tails are remnants of rotating wall compression and in many cases can remain unnoticed. We observe that the compression dynamics for a pure electron plasma behaves the same way as that of a mixed antiproton and electron plasma. Thanks to this optimized compression method and the high single shot antiproton catching efficiency, we observe for the first time cold and dense non-neutral antiproton plasmas with particle densities n ≥ 1013 m−3, which pave the way for an efficient pulsed antihydrogen production in AEḡIS. Graphical abstract Open image in new window